Electron-optical sectioning for three-dimensional imaging of crystal defect structures - Nellist, P (Elsevier, 2016)
The depth of field of an optical imaging system is proportional to the inverse square of the numerical aperture. The development of electron-optical devices to correct for the inherent spherical aberration of electron optics has led to a dramatic increase in numerical aperture that therefore also result in dramatic reductions in depth of field. The depth of field of a state-of-the-art system may now reach below 5 nm. An opportunity is therefore created to measure three-dimensional information about a sample by focusing on specific layers within the sample, a process known as optical sectioning. In this short review, we examine some of the properties of the technique, and illustrate its use with a range of applications to semiconducting materials that have been presented in the literature.